The Science, and Art, of Program Dissemination: Strategies, Successes, and Challenges. Issue 149 (September 2015) - McCoy, Kathleen P.
Abstract: The purpose of this special issue is to provide readers with a greater awareness of the processes involved in dissemination, as well as existing supports that help disseminate and sustain evidence‐based interventions. Although dissemination research is limited in most disciplines, it is particularly lacking in the social science field. Many interventions aimed to help children and adolescents are found to be efficacious every year, but program developers are often not equipped to understand how to scale up a program or sustain it after the initial funding. Consumers (e.g., service providers, who are consumers of interventions), on the other hand, often do not understand all that goes into implementing and scaling up an intervention. This special issue will: (a) introduce readers to the problem; (b) discuss some of the challenges with disseminating programs; and (c) present various existing supports that can help scale up and sustain interventions. © 2015 Wiley Periodicals, Inc.